Projections of subcontinental changes in seasonal precipitation over the two major river basins in South America under an extreme climate scenario - Gomes, Geraldo D.; Nunes, Ana M. B.; Libonati, Renata; Ambrizzi, Tércio (Climate dynamics, 2022)
The increase in the greenhouse gas emissions leads to changes in the mechanisms connecting the two major river basins in South America, the Amazon and La Plata basins, at subcontinental scale. Studies very often neglect to address the impact of the model-component choices on the projected change in precipitation in the two river basins. Within that context, the present study investigates the probable causes of changes in the hydroclimate of the two river basins through projections from three global climate models—driven by the pathway with no stabilization of the emissions growth by 2100—with focus on the warming of regions in the equatorial Atlantic and Pacific Oceans. Because the annual cycle of the precipitation differs in the northern and southern portions of the two river basins, changes are then preferably assessed in subregions. The model-dependent results project the following changes in the physical and dynamic mechanisms toward the end of the twenty-first century: (i) intensification of the 850-hPa northerly moisture flux from the western tropical Atlantic in the eastern side of the central Andes; and (ii) increase in the magnitude of the 200-hPa wind core whose location largely coincides with the La Plata basin. Those changes may increase the precipitation in the northern Amazon and southern La Plata basins by the end of the century. In contrast, the decrease in precipitation in the northern La Plata basin may result from the decrease in length of the rainy season associated with South American Monsoon System.